Simulasi Crowd Evacuation Menggunakan Kombinasi Social Force Model dan Attractive Potential Field - Evi Rokhayati; Mochamad Hariadi; Ahmad Zainul Fanani (Program Pascasarjana Magister Teknik Informatika, Universitas Dian Nuswantoro, 2019)
Natural disasters claimed many victims. To prevent this, one is to understand the problem of evacuation crowd behavior. Evacuation research in dangerous condition of the people or the crowd is a research to understand how human behavior in facing danger as individuals in a group or crowd. Evacuation research is almost impossible to be experimented in a real life, but it can be simulated. Evacuation simulation can help to understand more about the evacuation. For example, by understanding the evacuation, it could be used for the development of buildings and facilities safer and more comfortable or to make good standard evacuation procedures. Formerly research evacuation simulations in the crowd are based on the miSFM (mutual information Social Force Model) where the individual or agent in the crowd will conduct the evacuation simulation by using social force models and get feedbacks of mutual information such as location, rate, direction and density of agent, so there’s no effect of